Transformasi Program Penyuluh Agama Menangani Akar Masalah Kekerasan Anak dan Perempuan - Sahdani Ritonga (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This Policy Paper outlines the Cascading Program for Religious Instructors related to the eradication of violence against children and women. The lack of integrated training curriculum support, the absence of specific measurable performance indicators, and the lack of strong cross-sector coordination with child and women's protection agencies, so that this program is unable to reach the root of the social and cultural problems that cause violence. The objectives of this policy paper focus on 1) creating an integrated training curriculum synchronizing programs in terms of efforts to eradicate violence against children and women, and 2) establishing and creating specific measurable performance indicators 3) implementing strong cross-sector coordination with child and women's protection agencies. There are 3 (three) recommended policy alternatives, namely Alternative policies in the field of regulations, Alternative policies in the field of institutions and structures, alternative policies in the field of programs and implementation. Through the analysis of these policy alternatives, it can be concluded that program achievements at the Ministry of Religious Affairs can be realized if there is program synchronization and cascading performance in functional positions of religious instructors. Thus, the increasingly better performance of counselors will be able to resolve the problem of violence against women and children in the form of increasing the quality of family guidance services as well as fulfilling the activity performance indicator